N-n-butyl Haloperidol Iodide Protects against Hypoxia/Reoxygenation Injury in Cardiac Microvascular Endothelial Cells by Regulating the ROS/MAPK/Egr-1 Pathway - Lu, Shishi; Zhang, Yanmei; Zhong, Shuping; Gao, Fenfei; Chen, Yicun; Li, Weiqiu; Zheng, Fuchun; Shi, Ganggang (Frontiers in Pharmacology, 2017)
Endothelium dysfunction induced by reactive oxygen species (ROS) is an important initial event at the onset of myocardial ischemia/reperfusion in which the Egr-1 transcription factor often serves as a master switch for various damage pathways following reperfusion injury. We hypothesized that an intracellular ROS/MAPK/Egr-1 signaling pathway is activated in cardiac microvascular endothelial cells (CMECs) following hypoxia/reoxygenation (H/R). ROS generation, by either H/R or the ROS donor xanthine oxidase-hypoxanthine (XO/HX) activated all three MAPKs (ERK1/2, JNK, p38), and induced Egr-1 expression and Egr-1 DNA-binding activity in CMECs, whereas ROS scavengers (EDA and NAC) had the opposite effect following H/R. Inhibitors of all three MAPKs individually inhibited induction of Egr-1 expression by H/R in CMECs. Moreover, N-n-butyl haloperidol (F2), previously shown to protect cardiomyocytes subjected to I/R, dose-dependently downregulated H/R-induced ROS generation, MAPK activation, and Egr-1 expression and activity in CMECs, whereas XO/HX and MAPK activators (EGF, anisomycin) antagonized the effects of F2. Inhibition of the ROS/MAPK/Egr-1 signaling pathway, by either F2, NAC, or inhibition of MAPK, increased CMEC viability and the GSH/GSSG ratio, and decreased Egr-1 nuclear translocation. These results show that the ROS/MAPK/Egr-1 signaling pathway mediates H/R injury in CMECs, and F2 blocks this pathway to protect against H/R injury and further alleviate myocardial I/R injury.